Evaluation of Workplace Safety Culture Implementation and Practice Using Agglomerative Hierarchy Clustering - , George I. Akalonu; , Ify L. Nwaogazie; , Ejikeme Ugwoha (Archives of Current Research International, 2017)
This study assessed safety culture and practices in selected companies from the oil and gas, construction, transportation and logistics companies operating in the Niger Delta region of Nigeria. The questionnaire design utilized 15 safety cultural parameters and practices peculiar to 11 companies formed the basis of questionnaire distributed to 663 respondents in the study area. Purposive sampling was employed in the choice of companies sampled while random sampling technique was applied with respect to questionnaires distribution within the selected companies. XLSTAT 2016 statistical computer package was applied as aid for data analysis which includes Shapiro-wilks test of normality as an aid for the choice of analysis of variance option, the Friedman’s test to determine the variance among the various sampled groups which also includes a post-hoc test (Nemenyi’s Procedure) and Agglomerative Hierarchy Clustering (AHC) for clustering of workplace safety culture practices within the sampled groups. The output from the analysis of variance showed that there is a significant difference between the safety cultural practices of the three sampled industrial sectors with the alpha = 0.5 being lower than computed p-value (< 0.0001). Further analysis by AHC resulted in 4, 3 and 3 clusters of workplace safety cultural practices for oil and gas, construction and transportation and logistics sectors, respectively. The cultural practice were supervisors are authorized to stop unsafe work was identified as common between the construction and oil and gas sector while the practice of periodic hazards hunts and inspections by staff and management was identified as common among the construction and transportation and logistics industrial sector.